National Association for Universal Military Training records - National Association for Universal Military Training; Sheets, Henry Harrison; Association for National Service
Correspondence, financial records, and other records of the National Association for Universal Military Training and its predecessor, the Association for National Service, pertaining to the goals and operations of the organization. Also includes personal papers, chiefly correspondence (1904-1932), of the founder of the organization, Henry Harrison Sheets. Includes Sheets's correspondence with Edward S. Curtis pertaining to Curtis's work relating to the Indians of North America and his publication of the North American Indian. Other correspondents include S.B.M. Young, president of the national association, and Gutzon Borglum, George E. Chamberlain, Theodore Roosevelt, Elihu Root, Lorillard Spencer, and Leonard Wood.
Organization committed to universal military training and equal national service as the permanent military policy of the United States.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Borglum, Gutzon, -- 1867-1941 -- Correspondence; Chamberlain, George E. -- 1854-1928 -- Correspondence; Curtis, Edward S., -- 1868-1952. -- Correspondence; Curtis, Edward S., -- 1868-1952.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Spencer, Lorillard, -- 1883-1939 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Young, S. B. M. -- 1840-1924 -- Correspondence; Draft -- United States; Indians of North America; United States -- Armed Forces -- Recruiting, enlistment, etc; United States -- Military policy -- 20th century